An Overview of Public Anxiety to the COVID-19 Cases in the Arang Limbung, Kubu Raya West Kalimantan Province - Rahmawati, Annisa; Usman, Usman; Almumtahanah, Almumtahanah; Kawuryan, Uji; Ariyanti, Sri; Mardiyani, Ridha (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
COVID-19 or Severe Acute Respiratory Syndrome Coronavirus 2 (SARS Cov-2) is a global pandemic disease that attacks the respiratory system. Common signs and symptoms of COVID-19 include fever, cough, and shortness of breath. In addition to causing physical health problems, COVID-19 can also affect psychological health problems. Kubu Raya is an area affected by the Covid-19 and ever entered the red zone several times. The cases of COVID-19 will certainly arise anxiety in the community, especially death cases. The respondents were the people of Kubu Raya who were impacted by COVID-19. The study aimed to find out an overview of public anxiety to the impact of COVID-19 in Kubu Raya Regency. The research method was an analytic survey with a cross-sectional design. Sample selection technique used consecutive sampling with 90 respondents. The results of the univariate analysis showed the anxiety using the Anxiety Rating Scale (HARS) questionnaire that more than half of the respondents did not experience anxiety which was 56 people (62.2%). Mild anxiety was experienced by 18 respondents (20%). Followed by severe anxiety of 9 people (10%) and moderate anxiety of 7 people (7.8%). The finding hopefully provides benefits for hospitals and another health services, in the context of planning the development and implementation of nursing actions related to COVID-19. Moreover, it provided an overview of public anxiety. In the end, public anxiety can be minimized.